PEMBELAJARAN PKn BERBASIS MULTIKULURALISME PERSPEKTIF PSIKOLOGI SOSIAL ISLAM - Baidi Baidi (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2015)
This article describes a multicultural learning-based Civics insocial psychology perspective of Islam which includes the relationbetween; Civics with Islamic social psychology, Civics withmulticulturalism, Islam and multiculturalism Social Psychology,Civics with multiculturalism and social psychology Islam. Themethod used is descriptive qualitative to describe the relationship existing factsembaded design case study.The findings indicate that the diversity of the community is a necessity. Thediversity can lead to vulnerability to conflict. Some conflicts in various regionsrealize the importance of maintaining harmony in diversity. To prevent conflictsrequires an understanding citizens against multiculturalism in a diverse society.Understanding of multiculturalism can be taught through learning -based CivicsSocial Psychology perspective of multiculturalism in Islam. It is expected thatsmart and good citizenship is a manifestation of multiculturalism in theIndonesian context.